COMPARATIVE ANALYSIS OF CAR FOLLOWING MODELS BASED ON DRIVING STRATEGIES USING SIMULATION APPROACH - Vase Jordanoska; Igor Gjurkov; Darko Danev (MOBILITY & VEHICLE MECHANICS International Journal for Vehicle Mechanics , Engines and Transportation Systems, 2018)
Transportation and traffic affect all the aspects of everyday life. To better understand traffic dynamics traffic models are developed. On microscopic level, carfollowing models are developed and improved during long period of time. They are used in traffic simulation tools or are the basis for operation in some advanced vehicle systems. Carfollowing models describe traffic dynamics through movement of individual vehicle-driver units. This paper compares Gipps model and Intelligent Driver Model (IDM) as carfollowing models based on driving strategies. These models are derived based on assumptions such as keeping safe distance from the leading vehicle, driving at a desired speed and producing accelerations within a comfortable range. The models are implemented and simulated in MATLAB environment and the results are discussed in terms of the ability to reproduce real driving behaviour in car following scenarios.
Keywords: traffic dynamics, traffic simulation, car-following model, driving behaviour